Export pricing and the cross-country correlation of stock prices - Juha Tervala (Bank of Finland, 2009)
This study analyses cross-country correlations of stock prices (values of firms) using the basic New Open Economy Macroeconomics model. We show that cross-country correlations of stock prices greatly depend on the currency of export pricing in the case of monetary shocks but not notably for temporary technology shocks. In the case of a money supply shock, the producer (local) currency pricing version of the model generates a negative (positive) cross-country correlation of stock prices.
URN:NBN:fi:bof-20140807291
Keywords: 330